Daun Sukun dalam Ekspresi Karya Seni Lukis - Putra, I Made Adi Sumarjaya; Gunawan, I Wayan; Ruta, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
This MBKM Independent Project Report, with the title "Breadfruit Leaves in the Expression of Painting Art", departs from a breadfruit tree in I Made Sumadiyasa's studio which sparked the writer to create works of painting. The problem is how to visualize breadfruit leaves in each work. In its visualization, the writer uses the methods and techniques obtained from the MBKM process. The purpose and benefits are to develop the creativity of the writer in expressing imaginary forms and images/photos that are edited according to the needs of the writer in the work process. the author chooses I Made Sumadiyasa and I Ketut Budiana who are his favorite artists and uses his creation method which includes several stages, namely, contemplation, basic research, exploration, experimentation, execution, completion. From this process the author produced 7 works entitled: 1) "Voyage", 2) "Imagination", 3) "The Garuda", 4) "Soekarno", 5) "My Mother", 6) "Raincarnation", 7) " Zoom”. It can be concluded that the author created the work based on his interest in Breadfruit leaves, with ideas originating from phenomena captured in I Made Sumadiyasa's studio and reading reference sources from the internet. At the processing stage, the writer combines the techniques from the MBKM results and the techniques that the writer gets on campus, to be realized in a 2-dimensional form. It is hoped that from all these processes one can find identity in work.